Why Does It Snow? : Weather with the Very Hungry Caterpillar - Diaz, Joanne Ruelos; Carle, Eric (New York : World of Eric Carle, an imprint of Penguin Random House LLC, 2024)
Discover what makes snow fall.
new kids book 2024 winter.
Ages 1-3
Keywords: Snow -- Juvenile literature; Caterpillars -- Juvenile literature; Snow; Caterpillars; Board books; Butterflies, Moths & Caterpillars; Weather; Board books